Effect of Mg2+ and Mg2+/Li+ electrolytes on rechargeable magnesium batteries based on an erythrocyte-like CuS cathode. Issue 43 (3rd November 2020) - Ma, Yiming; Shuai, Kang; Zhou, Libing; Wang, Jin; Wang, Qiange
Abstract : An erythrocyte-like CuS electrode delivers a high capacity, higher rate capability, and superior cycling stability in ans Mg 2+ /Li + complex electrolyte. Abstract : Rechargeable magnesium batteries (RMBs) have been regarded as one of the most promising competitors for energy storage systems owing to their high volumetric density (3800 W h cm −3 ), earth abundance and safe metallic Mg anode. However, up till now, only a few cathode materials and suitable electrolytes could be used for RMBs, which has hindered the applications for rechargeable magnesium batteries. In this study, erythrocyte-like CuS nanosheet assemblies were prepared via a hydrothermal process and applied to RMBs with Mg 2+ and Mg 2+ /Li + complex electrolytes. Erythrocyte-like CuS|Mg 2+, Li + |Mg secondary batteries provide a stabilized capacity of 250 mA h g −1 without the activation process and excellent cycling stability over 500 cycles, which is superior to that in pure Mg 2+ electrolytes. Further, the reaction mechanism and kinetic analysis revealed that the addition of lithium salts could not only enhance the electrochemical performance but also effectively avoid the activation process. Considering the outstanding electrochemical performance of CuS in the Mg 2+ /Li + complex electrolyte, our study provides a new strategy for designing electrode structures and electrolyte composition for rechargeable magnesium batteries.